(untitled) (Journal of Engineering, 2008)
This paper presents a study to assess the degree of personal exposure to traffic generated pollutant emission along urban arterials in Mosul. The traffic flow characteristics (volume, speed, density, and vehicle type) were determined in the field at selected locations on the arterials.The vehicular traffic which includes (drivers, number of passengers in vehicles on the road, and pedestrian) exposed to road generated emissions were obtained through field survey.The vehicle emissions of CO, VOC, and NOx were calculated using air pollution estimation computer model (Mobile 4.1). It was concluded that the emission of CO, VOC, and NOx exceeds the standard level requirements. The risk arising from personal exposure to traffic generated emissions of such pollutants was analyzed and the degree of personal exposure of road users (drivers, passengers, and pedestrians) to pollutants emission along urban arterials in Mosul was determined.